Pembangunan Sistem Informasi Manajemen Perizinan di Dinas KOMINFO Kota Pasuruan - Anisah Evi Nur Rohmah; Denny Sagita Rusdianto; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
KOMINFO at Pasuruan is an institution that oversees the creation, maintenance and data security that related with information technology. KOMINFO serve making the system within the scope of government in Pasuruan. There are various system that have been made by KOMINFO, one of them is the city government website. DPMPTSP is one of agency in Pasuruan that serves the administration of licensing. In the licensing process, DPMPTSP encountered several obstacles such as the applicant file that was got accidently exchanged with the other applicants, too many permission application that also require high degree of accuracy, so making permission is longer. To overcome this, KOMINFO wants to create a website-based licensing system that can be accessed online. License to be made in this system: SIUP, TDP, TDUP and an advertisement. This system will be use to register permissions, view permissions status and validate permissions files. The result of requirement analysis is get 19 functional requirement and 1 nonfunctional requirement. Testing in this study using whitebox and blackbox for functional requirement. Whereas, the nonfunctional requirements are using compatibility testing. The result of testing, the valid value of each test case is performed which means that system is in accordance with requirement analysis.